أساليب التكيف مع الضغوط النفسية - مهرية, خليدة; حمادو, مسعودة (جامعة الوادي - University of Eloued, 2022)
تهدف الدراسة إلى الكشف عن العلاقة بين مصادر الضغوط وأساليب التكيف معها بين العامليين بالمؤسسة العمومية الاستشفائية تمنراست تبعا لمتغير الجنس والمناوبة الليلية، ولتحقيق أهداف الدراسة استخدمت الباحثتان مقياس الضغوط النفسية لأحمد عيد مطيع، ومقياس التكيف النفسي لكارفور على عينة عشوائية قوامها(89) عاملا، وكشفت نتائجها على عدم وجود علاقة بين مصادر الضغوط النفسية وأساليب التكيف النفسي لدى العاملين في المؤسسة الاستشفائية بمدينة تمنرست، وعلى وجود اختلاف بين العاملين في مصادر الضغوط النفسية بالمؤسسة الاستشفائية تبعا لمتغير الجنس(ذكور، إناث)، في حين لا يوجد اختلاف بين تبعا لمتغير المناوبة. The aim of the study is to uncover the relationship between stress sources and coping methods between the workers of the general hospital institution Tamanrast according to the variable sex and night shift. In order to achieve the objectives of the study, the researchers used the stress scale of Ahmed Eid Mateb and the psychological adjustment scale of K .Carver on a random sample of 89 workers, the results of which revealed that there was no relationship between stress sources and psychological adjustment techniques among staff of the hospital in the city of Tamnerst, and that there was a difference between staff of stress sources at the hospital depending on the gender variable.Male, female, while there's no difference between the shift variable.
دراسة ميدانية بمستشفى مصطفى بغدادي تمنراست
مقال
Keywords: الضغوط النفسية,التكيف النفسي,عمال قطاع الصحي; stress, psychological adjustment, health workers.